High proportion of mixed virus infections in raspberry plantations in Serbia - A. Paunović, Svetlana; Jevremović, Darko (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Samples of red raspberry (Rubus idaeus L.) from the most important growing areas in Serbia were analyzed for the presence of four most important raspberry viruses: raspberry leaf blotch virus (RLBV), raspberry leaf mottle virus (RLMV), black raspberry necrosis virus (BRNV) and Rubus yellow net virus (RYNV), and their incidence in individual and mixed infected samples. Seventy-four samples of eight raspberry cultivars, selected from 32 main cultivation sites were tested, of which 62 leaf samples showed symptoms that could be caused by viruses and 12 samples were asymptomatic. The presence of viruses was tested by appropriate RT-PCR and PCR methods, using virus-specific primers. All four viruses were detected with highly significant differences of incidence in a total of 61 infected symptomatic samples. Infection with one of the four tested viruses was detected in 59.0% of all infected samples. The most prevalent was RLBV, which was associated with raspberry leaf blotch disorder in coexistence with its vector raspberry leaf and bud mite P. gracillis, and it was detected in 70.5% of the infected samples. It was followed by RYNV with an incidence of 42.6%, BRNV with 36.1% and RLMV with 9.8% incidence, considering all infected samples. The obtained results for the first time in Serbia showed a high proportion (41.0%) of mixed infections involving between two and four viruses. The most common were infections with two viruses, 68.0% of all mixed-infected samples, and among them coinfections with RLBV and RYNV (44.0%). Viruses of the raspberry mosaic complex, BRNV, RYNV and RLMV, including coinfections of 2-3 listed viruses along with RLBV, were found in a high joined proportion of 14.7% of all infected samples, i.e. 36.0% of mixed infected samples.